Mechanical Integrators for Constrained Dynamics of Geometrically Exact Beams - Leyendecker, Sigrid; Betsch, Peter; Steinmann, Paul (Proc. Appl. Math. Mech. (PAMM), 2004)
The finite element formulation for nonlinear beams in terms of directors, providing a framework for the objective description of their dynamics, is considered. Geometrically exact beams are analyzed as Hamiltonian systems subject to holonomic constraints with a Hamiltonian being invariant under the action of SO(3). The formulation of the Hamiltonian systems in terms of the invariants of SO(3) is perfectly suited for a temporal discretization which leads to energy-momentum conserving integration. In this connection the influence of alternative procedures for the treatment of the constraints is investigated for the example of a beam with concentrated masse
UnivIS-Import:2015-04-16:Pub.2004.tech.FT.ltd.mechan